STUDY OF DOUBLE PROTONS MIGRATION MECHANISM IN SUPRAMOLECULAR STRUCTURES OF ACETIC ACID-WATER AND ACETIC ACID-AMMONIA BY AB INITIO METHOD - Karna Wijaya; Iqmal Tahir; Harnowo Harnowo (Universitas Gadjah Mada, 2003)
The theoretical study of double protons migration mechanism on acetic acid-water and acetic acid-ammonia associations has been carried out. The research covered determinations the reactant, transition state and product structures. To gain the goal, the research was conducted in three steps, i.e. (i) designing the reactant, transition state and product models, (ii) optimizing of structures, and (iii) calculating of their uncorrected total energy and frequencies with ab initio methods (basis set 6-31G**). All calculations were performed using Hyperchem ver 5.0 for Windows and Gaussian 94W package program. The computational study result showed that the calculated structures were in good agreement with the hypothetical structures.